Efficient polyfluorene derivatives for blue light-emitting diodes enabled by tuning conjugation length of bulky chromophores. (March 2022) - Guo, Feng; Zhang, Mingrui; Zhao, Sen; Hu, Liwen; Xiao, Biao; Ying, Lei; Yang, Renqiang
Abstract: In this work, a series of blue chromophores containing PAH core with different conjugation lengths and end-capped with diphenylamine were developed and introduced into PPF derivatives. Since the blue chromophores can enhance the thermal stability and suppress the interchain interactions efficiently, all copolymers present outstanding thermal decomposition temperatures up to 425 °C, high photoluminescence quantum yields (PLQYs) up to 48% and smooth surface morphology. Furthermore, the corresponding single-layer blue polymer light-emitting devices (PLEDs) based on these blue copolymers show good blue light emission peaking at 456–468 nm, and excellent stability of electroluminescence (EL) spectra. In particular, the best PLED with a maximum luminance of 8938 cd m −2, a maximum luminous efficiency ( LE max ) of 3.73 cd A −1, Commission International de L'Eclairage (CIE) coordinates of (0.14, 0.16) is achieved based on PPF-F . These results demonstrate that tuning the conjugation length of the bulky chromophores in blue light-emitting polymers is a novel and effective molecular design strategy toward highly stable and efficient blue polymer light-emitting diodes. Graphical abstract: Image 1 Highlights: High-performance blue light-emitting polymers for PLED are developed. Devices based on the designed polymers show stable blue emissions. Device based on PPF-F exhibits a maximum luminous efficiency of 3.73 cd A −1 .